Protection and the Business Cycle - Kyle Bagwell; Robert W. Staiger (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
Empirical studies have repeatedly documented the countercyclical nature of trade barriers. In this paper, we propose a simple theoretical framework that is consistent with this and other empirical regularities in the relationship between protection and the business cycle. We examime the ability of countries to maintain efficiency-enhancing reciprocal trade agreements that control their temptation to resort to beggar-thy-neighbor policies, under the requirement that such agreements are self enforcing. We find theoretical supposr for countercyclical movements in protection levels, as the fast growth in trade volume that is associated with a boom phase facilitates the maintenance of more liberal trade policies than can be sustained during a recession phase in which growth is slow. However, we also find that acyclical increases in the level of trade volume give rise to protection, implying that whether rising imports are met with greater liberalization or increased protection depends on whether they are part of a cyclic upward trend in trade volume or an acyclical increase in import levels.
Keywords: 330